Thermal degradation and flammability of nanocomposites composed of silica cross-linked to poly(methyl methacrylate). (20th October 2016) - Hatanaka, L. C.; Ahmed, L.; Sachdeva, S.; Wang, Q.; Cheng, Z.; Mannan, M. S.
Abstract : The effect of polymer cross-linkages on thermal degradation of silica/poly (methyl methacrylate) (PMMA) nanocomposites is investigated using a single novel nanoparticle. Nanosilica surface treated with KH570, an organic surface treatment capable of free-radical polymerisation, was used to cross-link PMMA via an in situ method. Scanning electron microscopy was used to characterise nanosilica before use, while X-ray diffraction confirmed silica was well dispersed in PMMA. Thermogravimetric analysis (TGA) results showed that thermal degradation of silica cross-linked nanocomposites was significantly stabilised compared to PMMA, with a 30% reduction in the peak mass loss rate. Kinetic studies revealed the degradation of nanocomposites in this work abide by first-order kinetics, with an increase in the degradation activation energy of approximately 100 kJ mol −1 . This is nearly double the improvement compared to conventional PMMA-silica nanocomposites in literature, showing dramatic enhancements to thermal stability. Analysis of high-temperature residuals from TGA tests suggest that cross-linked silica have increased char yields when compared with both PMMA and traditional silica nanocomposites. Cone Calorimetry results showed the materials in this work have reduced heat release rates compared to PMMA and traditional silica-PMMA nanocomposites.